(untitled) (Innovative professional education, 2024)
Actualize the importance of forming soft skills in future skilled workers in accordance with the prospects for the development of high-tech production and digital society. The concept of «soft skills» in the context of pedagogy, psychology, economics is studied and it is clarified that the soft skills of the future information and software operator integrate knowledge, skills and experience expressed through personal, communicative and activity components and ensure self-realization of the individual through interaction in the social and professional environment. The author analyzes the professional and state educational standard for the profession of «Information and software processing operator» and identifies the need to create favorable pedagogical conditions in vocational education institutions for more effective development of soft skills in future information and software processing operators.